2022
DOI: 10.3390/ijms232314540
|View full text |Cite
|
Sign up to set email alerts
|

Out of the Shadow: Blue Light Exposure Induces Apoptosis in Müller Cells

Abstract: Awareness toward the risks of blue light (BL) exposure is rising due to increased use of BL-enriched LEDs in displays. Short-wave BL (400–500 nm) has a high photochemical energy, leading to the enhanced production of reactive oxygen species (ROS). BL potentially plays a role in causing dry eye, cataracts, and age-related macular degeneration (AMD). The effect of BL on retinal pigment epithelium cells (RPEs) or photoreceptors has been extensively investigated. In contrast, only a few studies have investigated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…In laboratory settings on animal subjects and tissues, blue–violet light causes cumulative and lasting damage to retinal structures [ 15 – 17 ]. In particular, it causes oxidative stress that leads to the destruction of photoreceptor cells, which process light to create vision, and leads to apoptosis in primary Müller cells [ 18 ]. Most of the blue light research has studied varying blue–violet wavelengths from 405 to 455 nm.…”
Section: Resultsmentioning
confidence: 99%
“…In laboratory settings on animal subjects and tissues, blue–violet light causes cumulative and lasting damage to retinal structures [ 15 – 17 ]. In particular, it causes oxidative stress that leads to the destruction of photoreceptor cells, which process light to create vision, and leads to apoptosis in primary Müller cells [ 18 ]. Most of the blue light research has studied varying blue–violet wavelengths from 405 to 455 nm.…”
Section: Resultsmentioning
confidence: 99%
“…As already reported previously, especially Müller cells react very sensitive to BL exposure 3 and they are thought to play a role in oxidative-stress based retinal diseases like AMD. 3 , 4 , 5 , 6 To investigate, whether co-cultivation with a functional ppRPE-monolayer could have a beneficial effect in the BL-damage model and, more precisely on BL damaged Müller cells, we evaluated the expression of Glial Fibrillary Acid Protein (GFAP), indicating activated and thus stressed Müller cells. Enhanced activation of Müller cells ( GFAP expression) due to BL exposure dropped to control levels in co-cultivated explants, as demonstrated via qRT-PCR ( Figures 9 A and 9B).…”
Section: Expected Outcomesmentioning
confidence: 51%
“…Although it had previously been shown that exposure of pigmented rats to high-intensity blue light (8000 lx) [ 3 ] caused Müller cell hypertrophy and GFAP overexpression, our study shows that exposure to much less intense blue light causes similar effects. Although retinal neurons are more sensitive to blue-light-induced damage in vitro than Müller cells [ 54 ], recent studies have shown that exposure of Müller cells (in vitro) to low-intensity blue light can also cause apoptosis [ 55 ].…”
Section: Discussionmentioning
confidence: 99%